Family-Centered Tepid Water Sponging for Thermoregulation in Pediatric Complex Febrile Seizures: A Single-Case Study - Musviro Musviro; Selia Calita Putri; Nurul Hayati; Novela Eka Candra Dewi (Health and Technology Journal (HTechJ), 2026)
Febrile seizures in children, if prolonged and repeated, can cause serious complications for the child. Hyperthermia is a major nursing problem in children with febrile seizures, which can increase the risk of recurrent seizures if not treated immediately. A family-centered care approach is important in child care. The purpose of this study was to evaluate the use of tepid water sponges within a family-centered care approach to improve thermoregulation in children with febrile seizures. The research method was a case study. The participant in this study was a 3-year-old boy who was treated in the Bougenville Ward of Dr. Haryoto Lumajang Regional Hospital, with a medical diagnosis of complex febrile seizures, with nursing problems of hyperthermia and no history of allergies/extreme cold, the child did not have open wounds or severe infections, no dermatitis/severe eczema and the child did not experience severe respiratory disorders or unstable circulation. Data collection was conducted through interviews, observation, and documentation. The assessment results showed that the patient experienced increased body temperature, red skin, increased skin temperature, and tachycardia. The nursing problem that emerged was hyperthermia. The intervention carried out refers to the Indonesian Nursing Intervention Standards (SIKI), namely the management of external cooling hyperthermia using compresses soaked in tepid water, with a family-centered care approach. Family involvement is carried out through education and direct assistance during the action to increase family participation in child care. After 2 days of implementation, the results were a decrease in body temperature of 0.9–1.3°C, decreased redness, improved skin temperature, and decreased tachycardia. A tepid water sponge can help initiate peripheral vasodilation, increasing heat loss and lowering the child's body temperature. A tepid water sponge with a family-centered care approach can be used as a non-pharmacological intervention in the treatment of hyperthermia in children with febrile seizures